The Epistemological Aspects of Investigative Hypotheses - David Petretei (Institute of Medico-legal Publications Pvt Ltd, 2022)
This paper is about the philosophical and epistemological aspects of investigative hypotheses.Criminal investigation is a kind of cognition, so it is important to know the basic philosophic conceptof knowledge and truth. Different schools and traditions of philosophy have given different answers tothese.One of the basic elements of investigative thinking is, in addition to being reconstructive andretrospective, thinking in hypotheses. Logical, semantic, syntactic, epistemological, and ontologicalprinciples must be taken into account when formulating hypotheses. Choosing between the hypothesesshould be based on preference and indifference criteria. These criteria of preference and indifferencewill also be logical and epistemological.Testing, validating, and rejecting hypotheses is an essential element of investigative work. Theplausibility, credibility, and accuracy of competing hypotheses are constantly changing dependingon the investigative data obtained. It is a basic principle that all hypotheses should be tested and, ifpossible, the testing should be performed in parallel.